Provisions of Special Pardon and General Pardon in Syrian LawComparative Analytical Study (Damascus University Journal for legal sciences, 2024)
Pardon is the relinquishment of the social body from its right to punish those who commit criminal behaviour, and the consequences of this right, such as investigation and arrest of the perpetrator of the criminal behavior, his trial, and the imposition of punishment on him. Pardon in Syrian legislation is of two types: 1- A pardon for punishment, called 'special or individual pardon'. 2- A 'pardon for crime', called 'general pardon or amnesty.                                           A general amnesty is not granted except by the legislative authority, and it is issued only by law. As for the special pardon, it is issued by a decree from the head of the state, and it is of a personal character, because it is not issued by a specific crime or a group of specific crimes, but is issued by a person in his name, or by several people in their names, or in capacities that do not include other perpetrators of similar crimes. Most of the legislations in the world, including the Syrian legislation, consider the two institutions of 'special amnesty' and 'general amnesty', and the differences between these two institutions are great, and the effects of each of them are very different.              This study deals with the comparison between the legal regulation of the two institutions of 'special pardon'' and 'general pardon'' in the Syrian Arab Republic, by clarifying the nature of both the special pardon and the general pardon, and the provisions and effects of each according to what is stated in the Syrian law.
Keywords: Head Of State; Crime - Punishment; General Pardon; Special Pardon; The Legislative Authority; - The Pardon Committee